2014
DOI: 10.1542/peds.2014-0646j
|View full text |Cite
|
Sign up to set email alerts
|

The Association of Sugar-Sweetened Beverage Intake During Infancy With Sugar-Sweetened Beverage Intake at 6 Years of Age

Abstract: Sugar‐sweetened beverage (SSB) intake is associated with adverse health consequences including obesity and dental caries. Due to limited information on associations between SSB intake during infancy and intake of SSBs in childhood, we examined this question using longitudinal data for 1333 U.S. children from the 2005‐2007 Infant Feeding Practices Study II and the 2012 Follow‐up Study at 6 years of age. Multivariable logistic regression was used to calculate adjusted odds ratios (aOR) for associations of SSB in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
84
1
9

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 124 publications
(99 citation statements)
references
References 25 publications
5
84
1
9
Order By: Relevance
“…Among younger children, 12-23 months old, sweets and sweetened beverages provided 10.4% of total daily energy, and although the food groups were slightly different, this is similar to the 10.2% daily energy from sweetened foods and beverages reported in NHANES for the same ages [20]. Early consumption of sugar sweetened beverages is problematic not only by displacing more energy dense foods [2], but also because early consumption of sugar sweetened beverages significantly increases the likelihood of consuming them later in childhood [12], along with higher odds of developing obesity [30]. High consumption of discretionary calorie foods contributes to two significant public health problems, overconsumption of energy as well as inadequate intake of healthy foods from the basic food groups, such as vegetables, fruits and whole grains, and their associated nutrients [2].…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…Among younger children, 12-23 months old, sweets and sweetened beverages provided 10.4% of total daily energy, and although the food groups were slightly different, this is similar to the 10.2% daily energy from sweetened foods and beverages reported in NHANES for the same ages [20]. Early consumption of sugar sweetened beverages is problematic not only by displacing more energy dense foods [2], but also because early consumption of sugar sweetened beverages significantly increases the likelihood of consuming them later in childhood [12], along with higher odds of developing obesity [30]. High consumption of discretionary calorie foods contributes to two significant public health problems, overconsumption of energy as well as inadequate intake of healthy foods from the basic food groups, such as vegetables, fruits and whole grains, and their associated nutrients [2].…”
Section: Discussionsupporting
confidence: 54%
“…Early dietary habits are also associated with food preferences later in childhood [9][10][11]. This is true for fruits and vegetables [9][10][11] and also for less-healthy dietary components such as sugar-sweetened beverages and other sources of discretionary calories [10,12].…”
Section: Introductionmentioning
confidence: 99%
“…This lack of a dose-response relationship among SSB consumers may be due to the relatively low levels of SSB consumption among infants. 38 using the same data source found that the odds of SSB intake at 6 years was more than twofold greater among children who consumed any SSBs during infancy versus non-SSB consumers. Our additional analysis that included SSB intake at 6 years in the current multivariable model found a weaker but significant association between any SSB intake during infancy and obesity at follow-up.…”
Section: Discussionmentioning
confidence: 98%
“…SSB consumption differs significantly by age range. Multiple investigators have documented consumption beginning at young ages, including reports by Park that 25% of children studied consumed SSBs during infancy in a cohort of 1,189 US children (112), and these children had a higher likelihood of consuming SSBs at 6 years of age (115). In an analysis of NHANES data from 2007 to 2010, 62% of preschool children ages 2-5 years consumed SSBs daily compared with 73% of children ages 6-11 years and 76% of adolescents ages 12-19 years (15).…”
Section: Trends In Ssb Consumptionmentioning
confidence: 99%